Problem encountered by a large garment manufacturing company in subcontracting relationship - Rull, Ruby Armi Santos; Dizon, Angelita M. (1995.)
Problems are inevitable in every relationship. Thus, subcontracting relationship is not spared of the burden that problems bring in. Hence, this study was undertaken to shed more light into the problems encountered by a large garment manufacturing company in subcontracting relationship. Specifically, the study determined the problems and their causes. Some preventive measures for the perceived problems were also prepared. Data came through interviews or questionnaires given out to the Production personnel and the subcontractors; which totalled to 27 interviewees and/or respondents. Data gathered were analyzed using the Stream diagnostic Chart. The production personnel identified problems such as: late deliveries; quality defects; and subcontractors being choosy in style. On the other hand, the subcontractors' identified problems are: lat and short issuance of materials; delayed payments; complicated sewing operations; low sewing price; and unstable work load. Both sides agreed that miscommunication of instructions is also a problem. The problems are caused by the other problems mentioned; and that both sides are responsible for these problems. It was determined that all these problems resulted from communication deficiency. The primary suggestion was to deal with the communication problems --- management should have a better communication line with the subcontractors and within themselves. Consequently, other problems would be solved.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines -- Subcontracting